Can resistance training improve throwing performance in handball players? A Systematic review and meta-analysis - Hadjisavvas, S.; Efstathiou, M. A.; Themistocleous, I.-C.; Daskalaki, K.; Malliou, P.; Lewis, J.; Stefanakis, M. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Throwing is one of the most important movement in handball. Throwing performance is crucial for success in handball.